Justification for choosing the mediation and moderation variables in social sciences on entrepreneurship intention for Sudanese’s universities students - Abouh, Emad aldeen Essa; Ali, Idreis Elsiddig; Afifi, Osman Moh; Isamail, Monira Mohamed (Journal of Economic, Administrative and Legal Sciences, 2020)
The aim of this study is to highlight the concept of the mediation & moderation variables in social sciences on entrepreneurship intention for Sudanese’s universities students, how to choose, test and interpret. Where the response rate reached 88%, the study reached several results, the most important of which are: clarifying the most important justifications that require the choice of the mediation and moderation variables and the rate as well as the considerations that should be considered when studying these variables, as well as clarifying the way in which Use them and test those variables and interpret their results. The paper also provided some guidance that may help researchers to visualize the relationships between these variables, as well as provide a practical framework that enables them to fix the problems and remove the ambiguity and confusion that cover these concepts. We hope this paper fix the misconceptions related to these variables, testing and interpret, and also, work to create the atmosphere by providing some guidance that enables researchers to make decisions that help researchers in the testing these variables in social theories as well as work to expand the theory in the future.